Effect of soft segment molecular weight on the glass transition, crystallinity, molecular mobility and segmental dynamics of poly(ethylene oxide) based poly(urethane–urea) copolymers. Issue 65 (18th August 2017) - Oguz, Oguzhan; Koutsoumpis, Stefanos A.; Simsek, Eren; Yilgor, Emel; Yilgor, Iskender; Pissis, Polycarpos; Menceloglu, Yusuf Z.
Abstract : The effect of poly(ethylene oxide) (PEO) soft segment molecular weight ( M n = 2000, 4600, 8000 g mol −1 ) molecular mobility and segmental dynamics of a series of polyurethane–urea copolymers (PU) was investigated by dielectric relaxation spectroscopy. Abstract : The effect of poly(ethylene oxide) (PEO) soft segment molecular weight ( M n = 2000, 4600 and 8000 g mol −1 ) on the glass transition, crystallinity, molecular mobility and segmental dynamics of a series of aliphatic polyurethaneurea copolymers (PUU) with a constant hard segment content of 30% by weight was investigated using differential scanning calorimetry and dielectric relaxation spectroscopy. The soft segment (PEO) glass transition temperature increased with increasing molecular weight. Furthermore, five different relaxations were observed in dielectric analyses of all copolymers. These included local glassy state motions (γ) and (β), segmental motion of the soft phase (α), conductivity relaxation, and interfacial Maxwell–Wagner–Sillars (MWS) polarization. Local relaxations follow Arrhenius behavior and their time scale is not affected by the soft segment molecular weight. α-Relaxation follows Vogel–Tammann–Fulcher (VTF) behavior and is slower for the copolymer based on PEO-4600. Conductivity relaxation and the interfacial MWS polarization also follow VTF behavior and have quite similar slopes since both are related to the same phenomena. Unexpectedly, the interfacial MWS polarization is not affected by the soft segment molecular weight. Although this result suggests that the soft segment molecular weight does not affect the microphase separation in these copolymers, we believe that no safe conclusions can be extracted for this system due to the high complexity and the presence of many phases with different conductivity. However, significant differences were observed in the conductivity relaxation, which is much faster for the copolymer based on PEO-2000, due to its lower crystallinity when compared with others.